THE IMPLEMENTATION OF ROLE PLAY ON STEM IN THE NUCLEAR MATERIALS OF HEALTH TO IMPROVE STUDENTS' PARTICIPATION - Murniati, M; Saparini, S
This study aims at increasing students’ participation in role play strategy on STEM at Physics Education FKIP Unsri. This kind of research differs from other research designs. The issues raised are the problems faced by teachers during the classroom activities and some strategies are implemented to cope with the problems. Classroom Action Research is a sort of qualitative research even though the data collected may be quantitative. The data gained are described into words. The writer designed three cycles during the study The results showed that the 26% out of 14 students in the first cycle participated during the implementation of the strategy; 54% students’ participation were described, and gradually 83% students applied the strategy. Then, the students’ ability to comprehend and filter the information of Science, Technology, Engineering and Mathematics in each cycle was 26, 53 and 86. The study showed profoundly students got 60, 70, and 87 for technology; 50, 60 and 88 for engineering, and 25, 40 and 60 for mathematics. To conclude, the implementation of role play strategy on STEM can significantly increase students’ participation and ability to understand nuclear material in the environment.